Application of combined terrestrial laser scanning and unmanned aerial vehicle digital photogrammetry method in high rock slope stability analysis: A case study. (31st May 2022) - Ismail, Afiqah; Ahmad Safuan, A Rashid; Sa'ari, Radzuan; Wahid Rasib, Abd; Mustaffar, Mushairry; Asnida Abdullah, Rini; Kassim, Azman; Mohd Yusof, Norbazlan; Abd Rahaman, Norisam; Kalatehjari, Roohollah
Highlights: The conventional geological mapping in determining rock slope stability is risky and costly. The laser scanning and drone photogrammetric techniques allow it to overcome these issues by remotely collecting highly detailed point cloud data of a rock slope. This research compares the integration of Unmanned Aerial Vehicle (UAV) and TLS photogrammetry with traditional direct methods. The results show that both techniques provide accurate measurement and analysis compared to the traditional direct method. Abstract: Recent advancements in remote sensing techniques have made it possible to overcome the risky issues using conventional methods and have opened up new opportunities for collecting data on discontinuity characteristics. This research compares the application of a Terrestrial Laser Scanner (TLS) and Unmanned Aerial Vehicle (UAV) in rock slope stability analysis. Two case studies, Ulu Choh Quarry and Jelapang Rock Slope are analysed using Kinematic Analysis and Slope Mass Rating (SMR) to depict rock through the 3D point cloud. The techniques are compared with the hand mapping method concerning the accuracy of the data acquisition in assessing the rock slope. The standard deviation for the dip and dip direction between digital capture and hand mapping is 2.97° and 2.86°, which falls under the acceptable tolerance limit. The integration of UAV and TLS also generates excellent clear point cloud data from the top to the toe of the slope.